Hot rolling of light gauge steel strip - Zambrano, P. C.; Delgado, A. L.; Guerrero Mata, M. P.; Colás, R.; Leduc, L. A. (The Iron and Steel Institute of Japan, 2003)
Production of hot rolled thin gauge steel strip in a compact six-stand mill was studied by means of mathematical modelling and on site measurements. Data obtained during processing low carbon steel strip ranging from 1.06 to 2.68 mm in final outgoing thickness included speeds, reductions and separation forces at each of the six stands. The mean flow stress during rolling was calculated from the rolling loads, assuming adhesive conditions within the roll-gap, and by means of a mathematical model that accounts for strain hardening and the occurrence of various dynamic restoration phenomena during deformation. It was found that the values of the mean flow stress values, independently of the way they were obtained, varied as a function of both, strain rate and temperature, being possible to derive a unique formulation to describe their behaviour.